The correlations of rituals with pre-competition anxiety in teenage football players - Basiaga-Pasternak, Joanna (My University, 2017)
Aim. Rituals are sequences of thoughts and activities which lead to automatic performance [1]. They can sometimes be maladaptive. The aim of the study was to present the relationships between rituals before a football match and cognitive and somatic anxiety of young athletes. Basic procedures. The target group consisted of 100 football players, students of sports-profiled secondary schools. The following tools were implemented: Rituals in Sport, Routine Behaviour in Sport, Sport Anxiety Scale. Results and main findings. The study showed that the most common rituals are: “I touch the grass by my hand” and “I make the sign of the cross”. The study also showed that an increase in somatic and cognitive anxiety, concentration disruption and compulsive behaviours was correlated with the increasing level of rituals. Conclusions. Before sport competitions, rituals lead to a reduction of anxiety level but they cannot be inflexible in nature.
Keywords: psychologia sportu; lęk; piłka nożna; piłkarz; młodzież; rytuał; anxiety; rituals; football players